EP1133 Duration of chemotherapy for normalization of BHCG and treatment outcomes of gestational trophoblastic neoplasia at a tertiary cancer centre in Saudi Arabia. (1st November 2019) - Azam, F; Al-Selwi, W; Taha AbdelGhafar, W; Zahralliyali, A; AlWbari, A; Bukhari, N; Ibnshamsah, F
Abstract : Introduction/Background: Gestational trophoblastic neoplasia (GTN) constitutes rare group of benign and malignant neoplasia. BHCG (Beta human chorionic gonadotropins) is serum tumor marker that indicates a treatment response. This study is aimed to evaluate treatment outcomes, epidemiologic profiles and duration of chemotherapy for normalization of BHCG for (GTN) patients. Methodology: This retrospective study included GTN patients treated with chemotherapy at King Fahad specialist Hospital during the period January 2016-December 2018. Clinical data were collected patients electronic and paper files Results: Total of 22 patients with GTN received chemotherapy during the study period. Median age was 32 (18–53) years. 17 cases (77%) were diagnosed as GTN following molar pregnancy, and 5 (23%) cases were identified after abortion. GTN Stages of I, II, III and IV on diagnosis were noted in 12, 1, 7 and 2 patients respectively. According to WHO prognostic scoring system, 16 (72%) patients were classified as low risk, and 6(28%) as high risk. Intramuscular Methotrexate was the most frequently used first-line single-agent chemotherapy (n=16, 72%) for low risk disease, and EMACO regimen was the most frequently used combination chemotherapy (n=6, 28%) for high risk disease. The median number of chemotherapy cycles were 6 (1–16) and median duration of chemotherapy resulting in normalization of BHCG was 3 (1–8) months. Only 3 patients developed resistance to single agent chemotherapy and were switched to second line combination chemotherapy with median duration for normalization of BHCG of 6 months after chemotherapy switch over. 19 patients achieved complete response with first line and only 3 (14%) patients needed 2 nd line EMACO chemotherapy. All patients achieved complete response and currently on follow up. Conclusion: All patients achieved complete response with chemotherapy. Median duration of chemotherapy for normalization of BHCG was 3 months and 6 cycles. Only 3 patients required 2 nd line chemotherapy after single agent chemotherapy in 1 st line. Disclosure: Nothing to disclose